Elaboración de un plan de emergencias y desastres del centro integral de ingeniería ecológica (sitio sujeto a estudio) de la empresa bajo estudio, mediante la evaluación de la vulnerabilidad y amenaza - Arboleda Jácome, Viviana Gabriela (2015)
This work was performed at the site subject to study of the company under study what is located in the province of Francisco de Orellana, where it is carried out operational activities such as: Remediation of soil, contaminated sludge with hydrocarbon, treatment of hazardous waste not hazardous and special, and transportation of hazardous materials. It currently has basic Self-Protection Plan for fire response as requirements for operation permit stated by local Fire departament by the Fire Department, this document does not have a technical analysis of emergencies and threats that may arise during the implementation of different activities which perform daily in the company. With the application of the methodology Vulnerability Assessment Security (SVA) was obtained as a result 171 emergency situations, reflecting the amount is higher compared to the risk assessments that are commonly applied in Ecuador. Therefore, this method deepens in the study risk assessment for its excellent ability to throw results sistematic. With the information obtained settled measures of prevention and control for the development of Plan Emergency and Disasters